التحول الرقمي كألية لتدعيم التسويق السياحي و الفندقي - فتيحة, معنان; زهراء, كانش; كانش خميسي, براي (University of eloued جامعة الوادي, 2021)
"هدفت الدراسة إلى معرفة دور التحول الرقمي في تدعيم التسويق السياحي، حيث تضممتت الدراسمة لبعض الفتادق السياحية ، ودور وتأثي كل من التحول الرقمي والتسويق السياحي فيها، وذلك للوصمول إلى فهم أفضل لمدى تأثي التحول الرقمي على التسويق السياحي والفتدقي، وبيان مدى فاعلية التسويق السمياحي على أداء الفتادق السياحية ولتحقيق هذه الأهداف اعتمدنا في دراستتا على ثلاث فرضيات تمثلت في تحديمد المفهوم والعتاصر الأساسية لكل من التحول الرقمي والتسويق السياحي، بالإضافة إلى معرفمة دور التحمول الرقمي في تدعيم التسويق السياحي والفتدقي من خلال الخدمات السياحية التي تقدمها الفتادق والتي تؤثر على القطاع السياحي، وق د اعتمدنا على المتهج الوصفي في إزالة الغموض على بعض المفاهيم الخاصمة بمالتحول الرقمي، وكذلك تعريف التسويق السياحي ودعمه بالدراسات المتعلقة بالتحول الرقمي، والتسويق السياحي. وقد تم التوصل إن أن للتحول الرقمي تأثي كبي على الفتادق السياحية بسبب ظهور وتطور تكتولوجيا المعلومات والوسائل الرقمية التي أصبحت تعمم لبعض الفتادق، بالإضافة إلى التصميمات المتعلقمة بالتسمويق السياحي التي تعمل على تحقيق أهداف الفتادق السياحية بشكل أفضل.""The study aimed to know the role of digital transformation in strengthening tourism marketing, as it included the study of some tourist hotels and the role and impact of digital transformation and tourism marketing in them, in order to reach a better understanding of the impact of digital transformation on tourism and hotel marketing, and to show the effectiveness of tourism marketing on hotel performance. To achieve these goals, we relied in our study on three hypotheses, represented in defining the concept and basic elements of each of the digital transformation and tourism marketing, in addition to knowing the role of digital transformation in strengthening tourism and hotel marketing through tourism services provided by hotel that affect tourism marketing relying on the descriptive approach to demystify some concepts of digital transformation, as well as defining tourism marketing and supporting it with studies related to digital transformation. It has been concluded that digital transformation has a significant impact on tourist hotels due to the emergence and development of information technology and digital means that have become circulated for some hotels. In addition to designs related to tourism marketing that work to better achieve the goals of tourist hotels"
ماستر تسويق
Keywords: الفتادق السياحية، التحول الرقمي، التسويق السياحي; tourist hotels, digital transformation, tourism marketing.